Tradisi Maulid pada Masyarakat Muslim Gorontalo: Pertautan Tradisi Lokal dan Islam (Maulid Tradition Among Gorontalo Muslim Community: The Link Between Local Tradition and Islam) - Kamaruddin Mustamin; Muhammad Gazali Rahman; Arhanuddin Salim (Potret Pemikiran, 2021)
ABSTRACT This article aims to discover and probe deeper into the acculturation process of local culture with the practices and traditions of the maulid of the Prophet Muhammad in the Gorontalo community. This study uses a phenomenological qualitative approach. Data collection methods applied are in-depth interviews, observation, and documentation. The results of the study found that the presence and expansion of Islam in Gorontalo also influenced the religious perspective held by the people of Gorontalo. The willingness of the local community to adapt to the new teachings of Islam that they believe is a reinforcement of the acculturation of local cultural practices with the implementation of the tradition of the maulid of the Prophet Muhammad. The early Islamic preachers in Gorontalo managed to distinguish between the part of the local culture that still worth preserved and the part that must be preserved. This combination and acculturation effort between Islam and local culture is able to engender a new version and level of culture that is unique and has a local character. The innovative ability of the preachers to communicate Islamic rituals to the local culture of the Gorontalo people, can lead to a critical appreciation of the local values of the community's culture and the characteristics that accompany these values. Keywords: tradition; political; culture.ABSTRAKArtikel ini bertujuan untuk mengetahui dan menggali lebih dalam proses akulturasi budaya lokal dengan praktik dan tradisi maulid Nabi Muhammad saw. dalam masyarakat Gorontalo. Penelitian ini menggunakan pendekatan kualitatif fenomenologis. Metode pengumpulan data yang digunakan adalah wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menemukan bahwa kehadiran dan ekspansi Islam di Gorontalo turut mempengaruhi cara pandang keagamaan yang dianut oleh masyarakat Gorontalo. Kesediaan masyarakat lokal untuk mau beradaptasi dengan ajaran Islam yang baru mereka yakini menjadi penguat dari akulturasi praktik budaya lokal dengan pelaksanaan tradisi maulid Nabi Muhammad saw. Para pendakwah Islam awal di Gorotalo berhasil memilah antara bagian budaya lokal yang masih layak dipertahankan dan bagian yang harus dilestarikan. Upaya kombinasi dan akulturasi antara Islam dan budaya lokal ini mampu melahirkan versi dan level budaya baru yang khas dan bercorak lokal. Kemampuan inovasi para pendakwah mendialogkan ritual Islam dengan budaya lokal masyarakat Gorontalo, dapat mengantarkan diapresiasinya secara kritis nilai-nilai lokalitas dari budaya masyarakat beserta karakteristik yang mengiringi nilai-nilai itu.Kata kunci: tradisi; politik; budaya.